Subclavian and pulmonary artery steal phenomenon in a patient with isolated left subclavian artery and right aortic arch. Issue 4 (12th January 2012) - Hayabuchi, Yasunobu; Inoue, Miki; Sakata, Miho; Ohnishi, Tatsuya; Kagami, Shoji
Abstract We describe a patient with an isolated left subclavian artery associated with right aortic arch, patent ductus arteriosus, and ventricular septal defect. As the isolated left subclavian artery is supplied by the left vertebral artery in which blood flows in the retrograde direction, this anomaly is usually responsible for a congenital subclavian steal phenomenon. Atrophy of the left cerebral hemisphere and inverted left vertebral arterial flow were clearly depicted by echoencephalography in this patient, whose subclavian artery was connected to the main pulmonary artery by a patent ductus arteriosus. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound, 2013.